Starcross, or, The coming of the Moobs, or, Our adventures in the fourth dimension! : a stirring adventure of spies, time travel and curious hats - Reeve, Philip; Wyatt, David (New York : Bloomsbury Children's Books, 2007)
Young Arthur Mumby, his sister Myrtle, and their mother accept an invitation to take a holiday at an up-and-coming resort in the asteroid belt, where they become involved in a dastardly plot involving spies, time travel, and mind-altering clothing.
Wilson's Junior High School, January 2010.
School Library Journal, December 2007.
Horn Book Starred, April 2008.
Pub Weekly, November 2007.
Kirkus Starred, October 2007.
Booklist, November 2007.
Keywords: Resorts -- Fiction; Spies -- Fiction; Time travel -- Fiction; Brothers and sisters -- Fiction; Science fiction; Resorts -- Fiction; Spy stories; Time travel -- Fiction; Siblings -- Fiction; Science fiction; Resorts -- Fiction; Spies -- Fiction; Time travel -- Fiction; Brothers and sisters -- Fiction; Science fiction; Outer space -- Fiction; Outer space -- Fiction; Outer space -- Fiction